Volatile compounds from beneficial rhizobacteria Bacillus spp. promote periodic lateral root development in Arabidopsis. (18th February 2021) - Li, Yucong; Shao, Jiahui; Xie, Yuanming; Jia, Letian; Fu, Yansong; Xu, Zhihui; Zhang, Nan; Feng, Haichao; Xun, Weibing; Liu, Yunpeng; Shen, Qirong; Xuan, Wei; et al.
Abstract: Lateral root formation is coordinated by both endogenous and external factors. As biotic factors, plant growth‐promoting rhizobacteria can affect lateral root formation, while the regulation mechanism is unclear. In this study, by applying various marker lines, we found that volatile compounds (VCs) from Bacillus amyloliquefaciens SQR9 induced higher frequency of DR5 oscillation and prebranch site formation, accelerated the development and emergence of the lateral root primordia and thus promoted lateral root development in Arabidopsis . We demonstrated a critical role of auxin on B. amyloliquefaciens VCs‐induced lateral root formation via respective mutants and pharmacological experiments. Our results showed that auxin biosynthesis, polar transport and signalling pathway are involved in B. amyloliquefaciens VCs‐induced lateral roots formation. We further showed that acetoin, a major component of B. amyloliquefaciens VCs, is less active in promoting root development compared to VC blends from B. amyloliquefaciens, indicating the presence of yet uncharacterized/unknown VCs might contribute to B. amyloliquefaciens effect on lateral root formation. In summary, our study revealed an auxin‐dependent mechanism of B. amyloliquefaciens VCs in regulating lateral root branching in a non‐contact manner, and further efforts will explore useful VCs to promote plant root development. Abstract : The volatile compounds from Bacillus spp. increase the frequency of prebranch site formation and further accelerated the emergence of lateral root primordia (LRP) from the primary root (PR) in Arabidopsis, resulting in a denser lateral root (LR) along the PR spatially. This process is dependent on auxin signaling pathway; fully functional machinery of YUCs‐mediated auxin biosynthesis and polar auxin transport are also required.